The uniqueness of the 'flinstones' surau in Terengganu / Fadhlina Mahat, Arnieyantie Abdul Hadi and Rabiatul Adawiyah Abd Rahman - Mahat, Fadhlina; Abdul Hadi, Arnieyantie; Abd Rahman, Rabiatul Adawiyah (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2023)
An architecture that highlights extraordinary features will surely amaze anyone who looks at its beauty and uniqueness. This time I want to draw your attention to the architectural beauty of a surau that was built completely from the trunks of tembusu trees and old cengal wood that is over 500 years old.This surau is called Surau Langgar Rindu. Langgar means surau and longing, which means always longing to worship Allah SWT as taught by Prophet Muhammad S.A.W. This surau is located on the main Kuala Terengganu-Merang Road in Kampung Rhu, Tapai in Terengganu. The owner is Mr. Abdul Karim Embong who is 60 years old. He is a poet and an art activist.